Development and Implementation of a DECATASTROPHIZE platform and tool for the management of disasters or multiple hazards - Damalas, Andreas; Mettas, Christodoulos; Evagorou, Evagoras S.; Giannecchini, S.; Iasio, C.; Papadopoulos, Marinos; Konstantinou, Alexia; Hadjimitsis, Diofantos G. (My University, 2018)
Research studies using a Geo-Spatial Early Warning Decision Support System (GE-DSS) based platform and tool to integrate and link decision makers, Emergency Operation Centres (EOCs), Operational Resources (OR) in the field for multi-hazard or disaster management in accordance relative to the New European Union Civil Protection Mechanism (UCPM) priorities have neither been explored nor implemented. The goal of the DECATASTROPHIZE (DECAT) platform is to use a GE-DSS to assess, prepare for and respond to multiple and/or simultaneous natural and man-made hazards and disasters in a synergistic way on one multi-platform, distributed and integrated framework. The main results of the DSS platform include:1) GE-DSS use-case analyses, workflows and functionalities for early warning, decision making and rapid mapping, 2) methodologies for rapid assessment and mitigation of impacts, and 3) Spatial Data Infrastructures (SDI) from Cyprus for disseminating geospatial data and information about various types of multi-hazards with dedicated capabilities aimed to support impact assessment as well as emergency management based on activities suitable for overall operational scenarios. In addition to integrating the a) GE-DSS, b) EOCs, and c) OR in the field, the DECAT methodological framework software also integrated hazard/risk assessment with the common operational picture. The paper aims to introduce the GE-DSS prototype resulting from the implementation of these requirements, resulting by reuse, improvement and extension of Open Source SDI codes. It has been already tested in all of DECAT participating countries. The objectives achievement level was evaluated by analysing the test performed by Cyprus Civil Defense (CCD). The DECAT project aimed to a) demonstrate the assessment and mitigation of impact of natural disasters, b) discuss and develop effective warning systems decision making and rapid notification for risk resilience at all levels, c) stimulate exchange of ideas and knowledge transfer on all phases of the disaster management cycle including disaster research, and risk reduction at all geographical scales—local, national and international, d) assess multi-disaster risk and impacts from a multidisciplinary and multi-faceted perspective, e) develop multi-disaster risk reduction strategies and techniques.
Keywords: Disaster management; European Union (EU) Civil Protection Mechanism; Geo-spatial Early Warning Decision Support System; Humanitarian Aid and Civil Protection (ECHO); Multi-Hazard or Disaster Risk Assessment